2015
DOI: 10.1111/arcm.12226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Of Early Imperial Lacquerware From The Luozhuang Han Tomb, China

Abstract: This paper focuses on the characterization of materials from fragmented pieces of an imperial lacquer plate in the Luozhuang Han tomb, which dates to the early Western Han dynasty. Various non-invasive and minimally invasive techniques were performed, including optical and electron microscopy, XRF, Raman spectromicroscopy, FT-IR, XRD and THM-Py-GC/MS. The lacquerware pieces consist of a five-layer structure, which includes (from the top): a red pigmented layer, two lacquer finish layers, a ground layer and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…TMAH thermochemolysis is mainly the methylation of hydroxides of phenolic compounds, alcohols, saturated and unsaturated long-chain fatty acids, etc. [227,228]. Fig.…”
Section: Lacquer and Heritagementioning
confidence: 98%
“…TMAH thermochemolysis is mainly the methylation of hydroxides of phenolic compounds, alcohols, saturated and unsaturated long-chain fatty acids, etc. [227,228]. Fig.…”
Section: Lacquer and Heritagementioning
confidence: 98%
“…The lacquer is a natural resin chiefly composed of catechol derivatives that "polymerizes by the oxidation of urushiol with catalysts of laccase during the drying process" (Ma et al 2017). The composition of the lacquers varies according to the tree from which the sap is extracted, and, on this basis, it is possible to draw meaningful geographical distinctions:…”
Section: Cinnabar In Lacquered Objectsmentioning
confidence: 99%
“…In China, the oldest examples date back to the Chinese Neolithic age; however, the authors disagree on which is the oldest lacquered object found so far. Based on Ma et al (2017), the oldest example is represented by a black lacquered bowl dated to 8000 years BP, found at Kuahuqiao (Xiaoshan, Zhejiang). Based on Li et al (2009) and Wang et al (2018), the oldest example is represented by the cinnabar-containing lacquer-painted wood bowl found at the Hemudu site (Yu-yao, Zhejiang) and dated to more than 7000 years BP.…”
Section: Cinnabar In Lacquered Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lacquer tree is native to China and the Indian subcontinent, and it has been farmed for thousands of years in East Asian nations, such as Korea and Japan ( Fu et al., 2007 ; Nie et al., 2009 ). Historically, raw lacquer was traditionally produced of lacquerwares that were used as tableware and sacrificial utensils in Asian cultures ( Li et al., 2016 ; Ma et al., 2015 ). Currently, Chinese raw lacquer manufacturing accounts for 85% of the global total output value, and plentiful lacquer tree germplasm resources were available in China, such as “Dahongpao”, “Gaobachi”, “Huangmao Guizhou”, and “Hongmao Guizhou” etc .…”
Section: Introductionmentioning
confidence: 99%